Transporte electrónico en el grafeno con nanoporos y la presencia de moléculas - Aslla, A. P. (2013)
We analyze the electronic transport in a graphene nanodevice with a rectangular nanopore in the presence of different configurations molecules at the nanopore’s center. The behaviour of the electrons is described by the tight-binding method and the transport in the ballistic regime by the Landauer’s formula, where the electrical conductance is given by the transmission coefficient, which is determined using the non-equilibrium Green’s functions. The nanodevice is connected to two graphene semi-infinite contacts. The results show that the presence of molecules at the nanopore center produce resonance (antiresonance) in the profile of the transmission coeficient difference between nanodevice with and without molecule at the nanopore center. These resonances (antiresonances) are due to the coupling of the molecule discrete states and the continuum states of nanodevice also called as the Fano resonances.